Oocyte Competence Biomarkers Associated With Oocyte Maturation: A Review - Sirait, Batara; Wiweko, Budi; Jusuf, Ahmad Aulia; Iftitah, Dein; Muharam, R. (Frontiers in Cell and Developmental Biology, 2021)
Oocyte developmental competence is one of the determining factors that influence the outcomes of an IVF cycle regarding the ability of a female gamete to reach maturation, be fertilized, and uphold an embryonic development up until the blastocyst stage. The current approach of assessing the competency of an oocyte is confined to an ambiguous and subjective oocyte morphological evaluation. Over the years, a myriad of biomarkers in the cumulus-oocyte-complex has been identified that could potentially function as molecular predictors for IVF program prognosis. This review aims to describe the predictive significance of several COC biomarkers in evaluating oocyte developmental competence. A total of eight acclaimed cumulus biomarkers are examined in the study. RT-PCR and microarray analysis were extensively used to assess the significance of these biomarkers in foreseeing oocyte developmental competence. Notably, these biomarkers regulate vital processes associated with oocyte maturation and were found to be differentially expressed in COC encapsulating oocytes of different maturity. The biomarkers were reviewed according to the respective oocyte maturation events namely: nuclear maturation, apoptosis, and extracellular matrix remodeling, and steroid metabolism. Although substantial in vitro evidence was presented to justify the potential use of cumulus biomarkers in predicting oocyte competency and IVF outcomes, the feasibility of assessing these biomarkers as an add-on prognostic procedure in IVF is still restricted due to study challenges.